The innate immunity of a marine red alga involves oxylipins from both the eicosanoid and octadecanoid pathways - Bouarab, Kamal; Gaquerel, Emmanuel (Plant physiology, 2004)
The oxygenated derivatives of fatty acids, known as oxylipins, are pivotal signaling molecules in animals and terrestrial plants. In animal systems, eicosanoids regulate cell differentiation, immune responses, and homeostasis. In contrast, terrestrial plants use derivatives of C18 and C16 fatty acids as developmental or defense hormones. Marine algae have emerged early in the evolution of eukaryotes as several distinct phyla, independent from the animal and green-plant lineages. The occurrence of oxylipins of the eicosanoid family is well documented in marine red algae, but their biological roles remain an enigma. Here we address the hypothesis that they are involved with the defense mechanisms of the red alga Chondrus crispus. By investigating its association with a green algal endophyte Acrochaete operculata, which becomes invasive in the diploid generation of this red alga, we showed that (1) when challenged by pathogen extracts, the resistant haploid phase of C. crispus produced both C20 and C18 oxylipins, (2) elicitation with pathogen extracts or methyl jasmonate activated the metabolism of C20 and C18 polyunsaturated fatty acids to generate hydroperoxides and cyclopentenones such as prostaglandins and jasmonates, and (3) C20 and C18 hydroperoxides as well as methyl jasmonate did induce shikimate dehydrogenase and Phe ammonialyase activities in C. crispus and conferred an induced resistance to the diploid phase, while inhibitors of fatty acid oxidation reduced the natural resistance of the haploid generation. The dual nature of oxylipin metabolism in this alga suggests that early eukaryotes featured both animal- (eicosanoids) and plant-like (octadecanoids) oxylipins as essential components of innate immunity mechanisms.